Clashing dialectics of victimhood in Iraq War narratives: a comparative approach - M. Alosman, M. Ikbal; Raihanah, M. M. (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper examines the dialectics of victimhood and the associated liability for war atrocities in David Abrams’s Fobbit and Sinan Antoon’s The Corpse Washer. It contrasts the perspectives of Abrams, an American veteran of the 2003 war in Iraq, with Antoon, an Iraqi civilian, shedding light on their differing portrayals of the American-led invasion. Victimhood serves as a central theme in war narratives, providing both justification for violence and a means to absolve aggressors of accountability for subsequent atrocities. This study explores the intricate interplay between self-perceived victimhood and narrative construction in the context of the Iraq War. The methodology focuses on concepts of victimhood, the psychological impact of war, and the assertion of narrative ownership. The findings illustrate that while Abrams’s narrative adopts an outsider perspective and portrays Americans as the most visible victims—often absolving them of complicity—Antoon’s work presents an insider perspective that emphasizes the profound humiliation intertwined with death in Iraq. In The Corpse Washer, death transcends mere grief, becoming a symbolic representation of the enduring suffering and degradation faced by the Iraqi people, thereby framing American presence as a source of relentless destruction and moral conflict. This perspective challenges readers to confront the complexities of war, emphasizing the moral implications of foreign intervention and the profound costs borne by the Iraqi people.